2000
DOI: 10.1016/s0304-3959(00)00233-5
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic profile of the nicotinic acetylcholine receptor agonists, (+)-epibatidine and ABT-594 in models of persistent inflammatory and neuropathic pain

Abstract: The anti-nociceptive and locomotor effects of the nicotinic acetylcholine receptor (nAChR) agonists (+)-epibatidine and ABT-594 were compared in the rat. Acute thermal nociception was measured using the tail flick test. Mechanical hyperalgesia was measured as paw withdrawal threshold (PWT) in response to a mechanical stimulus in two animal models of persistent pain; (1) 24 h following subplantar injections of Freund's complete adjuvant (FCA) into the left hind paw or (2) 11-15 days following a partial ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 5 publications
3
33
0
2
Order By: Relevance
“…The functional activity of ABT-594 at the human muscle type of nicotinic receptor was quite unexpected since this compound has been shown to have a 180,000-fold specificity for recombinantly expressed human α4β2 compared to Torpedo α1β1γδ receptors (Donnelly et al 1998). The functional activation of the neuromuscular receptor by ABT-594 is reflected in in vivo experiments where it has been demonstrated that higher doses of ABT-594 disrupt performance in the rotarod test, although the separation between motor and anti-hyperalgesic effects is clearer compared to epibatidine (Kesingland et al 2000). GTS21 and AAR17779 have been described as specific α7 receptor agonists (De Fiebre et al 1995;Levin et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The functional activity of ABT-594 at the human muscle type of nicotinic receptor was quite unexpected since this compound has been shown to have a 180,000-fold specificity for recombinantly expressed human α4β2 compared to Torpedo α1β1γδ receptors (Donnelly et al 1998). The functional activation of the neuromuscular receptor by ABT-594 is reflected in in vivo experiments where it has been demonstrated that higher doses of ABT-594 disrupt performance in the rotarod test, although the separation between motor and anti-hyperalgesic effects is clearer compared to epibatidine (Kesingland et al 2000). GTS21 and AAR17779 have been described as specific α7 receptor agonists (De Fiebre et al 1995;Levin et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The α4β2 subtype-selective ligands were the first to be developed. ABT-594, which is a structural analogue of epibatidine, was shown to be a potent full agonist for the α4β2 nAChRs with a strong analgesic effect [158, 163, 164]. In various animal models of pain, the analgesic activity of ABT-594 was inhibited by the administration of the general antagonist mecamylamine [162, 165].…”
Section: Painmentioning
confidence: 99%
“…In addition to its clear nociceptive role, nicotinics may be able to confer a degree of analgesia (Carstens et al 2001;Kesingland et al 2000;Reuter et al 2003). These influences might arise from modulation of peptide release (Bannon et al 1998a,b;Donnelly-Roberts et al 1998), cross desensitization (Sudo et al 2002), tachphylaxis (Dessirier et al 2000;Jinks and Carstens 1999), or direct interaction with voltage-dependent channels (Liu et al 2004).…”
Section: Introductionmentioning
confidence: 99%